Evaluation of wheat middlings-based supplements at different crude protein concentrations for cattle consuming winter range forage - G.D. Sunvold; R.C. Cochran; E.S. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1990)
Influence of increasing crude protein concentration in a wheat middlings-based supplement was evaluated in an intake/digestion trial. Protein-supplemented steers demonstrated increased (P<.01) intake of dormant, bluestem-range forage when compared with unsupplemented steers. Although increasing concentration of supplemental crude protein from 15 to 20% substantially increased (P<.01) forage and total dry matter intake. only slight increases in forage and total dry matter intake occurred when the concentration exceeded 20%. Protein supplementation increased (P<.01) fiber and dry matter digestibilities. Additionally. fiber digestibility tended (P=.087) to increase with increasing crude protein concentration of the supplement. Results suggest that when feeding a wheat middlings-based supplement. the crude protein concentration should be 20% or higher to optimize use of poor-quality forage.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Protein; Supplementation; Wheat middlings; Intake; Digestibility; Winter range